Lumumba, Hammerskjoeld and the 1960 Congo Crisis: a Case of International Misunderstanding? - Blommaert, Jan (Afrika Focus, 1990)
A number of influential works on the 1960 Congo Crisis, as well as most theoretical models of intercultural communication, consistently explain conflicts between cul- turally different participants in terms of features of ethnic communication style, cognition, value systems etc. A general picture emerges in which culture is seen as the cause of conflicts, misunderstandings, or communication breakdown. An ana- lysis of six letters exchanged between Lumumba and Hammarskjoeld during one of the crucial episodes of the Congo Crisis reveals that ethnic features of communica- tion style are the consequence, rather than the cause of conflicts. KEY WORDS: Congo (Zaïre), history, linguistics